2017
DOI: 10.1111/cas.13304
|View full text |Cite
|
Sign up to set email alerts
|

Calcitriol exerts an anti‐tumor effect in osteosarcoma by inducing the endoplasmic reticulum stress response

Abstract: Osteosarcoma is the most common type of primary bone tumor, and novel therapeutic approaches for this disease are urgently required. To identify effective agents, we screened a panel of Food and Drug Administration (FDA)‐approved drugs in AXT cells, our newly established mouse osteosarcoma line, and identified calcitriol as a candidate compound with therapeutic efficacy for this disease. Calcitriol inhibited cell proliferation in AXT cells by blocking cell cycle progression. From a mechanistic standpoint, calc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
34
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 17 publications
(34 citation statements)
references
References 44 publications
0
34
0
Order By: Relevance
“…These results suggest that 1,25D 3 does not modulate active cytochrome c oxidase via COXII and COX4I1 subunits at the transcriptional level. These results point to alternative mitochondrial regulators, including perhaps other components of the electron transport chain, in the regulation of ROS by vitamin D 25 .…”
Section: Resultsmentioning
confidence: 82%
See 3 more Smart Citations
“…These results suggest that 1,25D 3 does not modulate active cytochrome c oxidase via COXII and COX4I1 subunits at the transcriptional level. These results point to alternative mitochondrial regulators, including perhaps other components of the electron transport chain, in the regulation of ROS by vitamin D 25 .…”
Section: Resultsmentioning
confidence: 82%
“…Although CYP24A1 is commonly upregulated in cancers and thought to be one mode for vitamin D resistance 32 , this appears not to be the case for MG-63 cells treated with 100nM 1,25D 3 based on the MTT results ( Figure 1A ). This suggests other anti-cancer strategies upon high levels of vitamin D, including apoptosis 33 and/or induction of other stress pathways such as those involving the endoplasmic reticulum 25 .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…However, there are several studies that have looked at the role of vitamin D on ROS production and detoxification. For example, a recent paper has shown that supraphysiological levels of calcitriol exerts its anti-tumor effects in a mouse cell model of osteosarcoma via induction of the endoplasmic reticulum stress response with a concomitant increase in intracellular ROS 25 . In addition, cDNA microarray analysis using human prostate epithelial cells revealed that calcitriol (50nM) can promote SOD2 expression (2.01 fold increase, 24 hours) 26 , as well as the early expression of the antioxidant thioredoxin reductase 1 (TXNRD1; 2.8 fold increase, 6 hours) 27 .…”
Section: Introductionmentioning
confidence: 99%